Agricultura de precisión en el manejo agronómico del cultivo de maíz - Contreras Velásquez, Ronald Eduardo (2020)
SUMMARY The research was developed through a descriptive and bibliographic research; the information was obtained from scientific publications and other digital documents that have a direct relationship with the subject of the research work "Precision agriculture in the agronomic management of maize cultivation on the Ecuadorian coast", whose objective is to identify the technologies applied in maize production on the Ecuadorian coast. Taking into account the results of research carried out, after being analyzed, the conclusion was reached: in maize crops on the Ecuadorian coast precision farming methods are not applied, therefore it is recommended to intervene with research and other methods that would contribute with the production of yellow maize and environmental care with the use of variable dose technologies , GPS-assisted spraying, GIS programs, statistical programs, GPS global positioning systems, remote sensors, direct sensors.